2015
DOI: 10.21061/jots.v41i1.a.5
|View full text |Cite
|
Sign up to set email alerts
|

<p>Value of Informal Learning Environments for Students Engaged in Engineering Design</p>

Abstract: A focus group study was conducted with purposefully sampled student participants solving an engineering design challenge during a one-week engineering summer camp held at a research-intensive university in the southeast. The goal of the study was to further understand the student experience and ascertain the perceived value of an informal learning environment for students engaged in an engineering design challenge. Emergent themes are provided to illustrate the primary challenges related to the engineering des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Students reported that as a result of their participation, their interest in engineering careers and their interest in pursuing a 4-year degree increased. Denson, Lammi, White, and Bottomley (2015) convened a focus group "to further understand the student experience and ascertain the perceived value of an informal learning environment for students engaged in an engineering design challenge" during a summer camp (p. 40). The eight high school students who participated in the study reported that they perceived "the benefits of the summer camp to include the use of mathematical modeling (application of math and science), a field experience, and teamwork" (p. 43).…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%
“…Students reported that as a result of their participation, their interest in engineering careers and their interest in pursuing a 4-year degree increased. Denson, Lammi, White, and Bottomley (2015) convened a focus group "to further understand the student experience and ascertain the perceived value of an informal learning environment for students engaged in an engineering design challenge" during a summer camp (p. 40). The eight high school students who participated in the study reported that they perceived "the benefits of the summer camp to include the use of mathematical modeling (application of math and science), a field experience, and teamwork" (p. 43).…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%
“…Formal learning environments such as schools have been limited in addressing these barriers to STEM interest and advancement among underrepresented youth (Denson et al, 2013). However, a growing body of research has demonstrated that informal learning environments can successfully increase students' knowledge and skills relating to STEM (Chubin et al, 2005;Eshach, 2007;Denson, Austin et al, 2015;Denson, Lammi et al, 2015). Informal STEM programs such as those that occur after school or during the summer have potential to improve interest in STEM, alongside soft skills and literacies that are important for navigating life in the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Informal STEM programs such as those that occur after school or during the summer have potential to improve interest in STEM, alongside soft skills and literacies that are important for navigating life in the 21st century. In contrast to the procedural constraints of formal educational settings, informal learning programs are flexible, can be built around fun and engaging activities, and can be structured to encourage team-based and collaborative work (Denson, Austin et al, 2015;Denson, Lammi et al, 2015). Informal STEM programs can also expose students to professionals from underrepresented groups who are working in STEM fields (Denson, Austin et al, 2015;Denson, Lammi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange of information and sharing of experience helps learning -even in the absence of explicit planning by instructors [15] . Equally important, Denson et al [16] reported a learning experience of a student-formed group that was useful in developing their mathematical modeling skills.…”
Section: Introductionmentioning
confidence: 99%